AdvanCE, a capsule endoscope delivery device, is effective in investigating a waterfall stomach. Issue 2 (1st February 2023) - Miyaguchi, Kazuya; Tsuzuki, Yoshikazu; Imaeda, Hiroyuki
Abstract: AdvanCE is a useful device in patients who cannot swallow capsule endoscopes, or when these remain in the patient's stomach without passing into the duodenum. A net or snare may be used to guide the capsule endoscope into the duodenum when the capsule endoscope becomes stuck in the stomach, but it may be difficult to guide the capsule into the duodenum in some cases, particularly in those of waterfall stomach. In such cases, AdvanCE is found to be an effective guidance tool. Abstract : The capsule endoscopy was brought to the duodenum with AdvanCE using a guidewire as a landmark for the waterfall stomach.